A first-principles study on the hydrogenation of acetone on HxMoO3 surface. (23rd April 2019) - Pan, Qiyun; Huang, Liang; Li, Zhong; Han, Juanjuan; Zhao, Nian; Xie, Yunlong; Li, Xiang; Liu, Meifeng; Wang, Xiuzhang; Liu, Jun-Ming
Abstract: Hydrogenation of acetone on the (010) surface of hydrogen molybdenum bronzes was investigated by density functional theory (DFT) calculations with periodic slab models. The formation of H-bond between the carbonyl oxygen of acetone and the terminal OH group of the surface leads to a stable adsorption of acetone. The effect of hydrogen concentration in the bronzes on the hydrogenation of acetone was systematically investigated, indicating the hydrogenation reaction is a one-step concerted and exothermic process regardless of the hydrogen contents in the bronzes surface. The 8H surface with increased H-content shows a significantly exothermic reaction process and exhibits the smallest kinetic barrier compared with 4H or 6H surfaces. Additionally, the selectivity for hydrogenation acetone could increase owing the absence of CC bond activation. The findings in this study can help with designing of high-efficient and low-cost metal oxide catalysts for hydrogenation of unsaturated substances. Highlights: Hydrogenation of acetone on the molybdenum oxide hydrogen bronzes surface was investigated. The mechanism of hydrogenation process was one-step concerted and exothermic. Increase of H concentration (i.e., 8H surface) expectedly decreases the kinetic barrier.